Multifunctional energy storage and piezoelectric properties of 0.65Pb(Mg1/3Nb2/3)O3–0.35PbTiO3 thick films on stainless-steel substrates. (1st April 2022) - Sadl, Matej; Nadaud, Kevin; Bah, Micka; Levassort, Franck; Eckstein, Udo; Khansur, Neamul H; Webber, Kyle G; Ursic, Hana
Abstract: The miniaturization of electronic devices and power systems requires the fabrication of functional components in the form of micrometer-sized thick films. A major challenge is the integration of functional ceramics with metals, which are considered incompatible with high-temperature ceramic processing. To overcome the integration barrier, an aerosol deposition (AD) spray-coating method based on room temperature deposition can be used. By employing the AD method, we were able to deposit relaxor-ferroelectric 0.65Pb(Mg1/3 Nb2/3 )O3 –0.35PbTiO3 ceramic thick films on low-cost stainless-steel substrates. The as-deposited films were dense, with ∼97% of the theoretical density. Moreover, the post-deposition annealing at 500 °C did not result in any microstructural changes. Compared to the as-deposited films, the annealed films exhibit improved energy storage and electromechanical properties. The annealed thick films achieve a recoverable energy density of 15.1 J⋅cm −3 at an electric field of 1350 kV⋅cm −1 and an electric-field cycling stability of 5 million cycles. A piezoelectric response was detected through the entire film thickness by piezoelectric force microscopy. Macroscopic displacement measurements revealed a maximum relative strain of 0.38% at 1000 kV⋅cm −1, corresponding to inverse effective piezoelectric coefficient of ∼40 pm⋅V −1 . In this study, we overcame the integration challenges and demonstrated the multifunctionalization of future ceramic-metal structures, as the deposited thick films on stainless steel exhibit energy storage capability and piezoelectric properties.